Bupleurum iranicum (Apiaceae), a new species from Talesh Mountains, northwestern Iran - Bidarlord, Mahmoud; Kljuykov, Eugene; Lyskov, Dmitry (Phytotaxa, 2023)
A new species, Bupleurum iranicum (Apiaceae), is described from Ardabil Province, northwestern Iran. The new species is similar to B. anatolicum and B. brachiatum in the narrow, linear cauline leaves, herbaceous bracts similar to bracteoles, bracteoles shorter than the flowers, fruit surface, and petals smooth, and number of umbel rays 2–3. At the same time, the new species differs from the above-mentioned taxa in features of the stem features (non-branched or slightly branched vs. diffusely or dichotomously branched), umbel rays (subequal vs. unequal), length and number of bracts (equal 1–2 vs. subequal 2–5), and shape (elliptic to ovate vs. lanceolate). A detailed description and comparisons with other similar taxa, color images, distribution and habitat, and a taxonomic key to the Bupleurum species from Iran are provided. The new species should be listed as Critically Endangered, its protection is therefore recommended.